2016
DOI: 10.1007/s00334-016-0596-5
|View full text |Cite
|
Sign up to set email alerts
|

High-resolution palynology reveals the land use history of a Sami renvall in northern Sweden

Abstract: The limited availability of historical and archaeological evidence means that much is still unknown about the development of Sami reindeer herding in Fennoscandia in both the recent and more distant past. To address this problem, high-resolution palynological analyses, 14 C and 210 Pb dating were undertaken on two adjacent (\25 m apart) peat profiles collected at a recently abandoned reindeer gathering pen (renvall) near Jokkmokk (*66.6°N, 19.8°E) in the boreal forest of northern Sweden. The aim was to assess … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 70 publications
1
18
0
Order By: Relevance
“…Even when considering Sporormiella and Sordaria together, however, Ruppert Lake and Woody Bottom Pond did not show the same temporal pattern of abundance. Although appearing counter-intuitive because these two sites are located close together, this result reinforces earlier findings that the dung fungal spore signal can relate to extremely small spatial scales (e.g., Kamerling et al, 2017; Davies, 2019). This may be explained by the observation of Baker et al (2016), who found that shore run-off (within <10 m distance from the water) was the most significant process transporting spores into a series of ponds in the Oostvaardersplassen nature reserve in the Netherlands.…”
Section: Discussionsupporting
confidence: 87%
“…Even when considering Sporormiella and Sordaria together, however, Ruppert Lake and Woody Bottom Pond did not show the same temporal pattern of abundance. Although appearing counter-intuitive because these two sites are located close together, this result reinforces earlier findings that the dung fungal spore signal can relate to extremely small spatial scales (e.g., Kamerling et al, 2017; Davies, 2019). This may be explained by the observation of Baker et al (2016), who found that shore run-off (within <10 m distance from the water) was the most significant process transporting spores into a series of ponds in the Oostvaardersplassen nature reserve in the Netherlands.…”
Section: Discussionsupporting
confidence: 87%
“…Contrasting with current practices with relatively free‐ranging reindeer, the earlier common form of reindeer herding (AD ~1350–1900 in Padjelanta area; Aronsson ) was nomadic and involved tame reindeer herds traveling close to the herders through the mountain landscape during summer (Aronsson , Kamerling et al. ). Along their travel route, herders regularly occupied the exact same locations, which were intentionally selected and constructed for the needs of reindeer herding (e.g., loose stones and shrubs cleared away; Aronsson ).…”
Section: Methodsmentioning
confidence: 99%
“…Lake sediments consist of both autochthonous (in-lake) and allochthonous (from the catchment and beyond) organic and inorganic matter. Paleoecological inquiries using biological archives stored in lake sediments have been largely dominated by microscopic analyses of the relatively limited number of aquatic and terrestrial groups that leave wellpreserved and readily identifiable morphological remains in the sediment (e.g., silicified diatoms, calcified nannofossils, organic walled or calcified dinoflagellates, chrysophytes cysts, Cladocera remains, chironomid head capsules, fungal spores, pollen and plant macrofossils) [1][2][3][4][5][6][7][8][9], keeping the remaining biological diversity out of reach. Where these morphological remains are not well preserved or cannot be taxonomically identified to the species level, alternative proxies have been sought to build a more detailed and comprehensive understanding of past biological diversity in a broader range of environments [10,11].…”
Section: Sedimentary Dna a Powerful Proxy To Track Past Biodiversitymentioning
confidence: 99%